C, N co-doped Co3O4 hollow spheres prepared via hydrothermal reaction for improved electrochemical activity. (1st January 2020) - Wang, Yinwei; Huo, Jiaofei
Abstract: Superior electrode materials play a key role on the electrochemical performance for the lithium-ion batteries and supercapacitors. The Co3 O4 -based materials are promising electrode materials due to their high specific capacity and energy density. However, the poor cycle performance limits their applications during the process of the commercialization for the lithium-ion batteries and supercapacitors. Because of the poor cycle stability, C, N co-doped Co3 O4 hollow spheres are successfully prepared and used as electrode materials for the lithium-ion batteries and supercapacitors. Via the C, N co-doping process, the electronic conductivity is greatly improved. Moreover, the hollow structure could ensure the structural stability during the electrochemical process. As a result, the cycle performance and specific capacity are greatly improved when the C, N co-doped Co3 O4 composites are used as electrode materials for the lithium-ion batteries and supercapacitors. Highlights: C, N co-doped Co3 O4 hollow spheres are successfully prepared and used as electrode materials. The hollow structure could ensure the structural stability during the electrochemical process. The cycle performance and specific capacity are greatly improved.